Analysis and prediction of tensile properties based on rule of mixtures model for multi-scale ramie plain woven fabric reinforced composite. (1st May 2023) - Zuo, Qi; Wang, Chunhong; Pei, Xiaoyuan; Lin, Ligang; Li, Yonggang; Sun, Weidi
Highlights: Tensile properties of multi-scale yarn-based woven fabric reinforcements and their composites were investigated. ROM model was improved by yarn packing density and crimped angle of yarn to adapt the woven fabric reinforced composite. Relationship among structures from macro to micro dimensions of ramie plain woven fabric reinforced composite was revealed. Abstract: Natural fibers are increasingly used as sustainable reinforcement for composites because of their carbon capture and renewability. Classical rule of mixtures (ROM) and ROM-based models have been widely used to predict the tensile properties of natural fiber reinforced composites with random or unidirectional oriented structures. However, the woven fabric reinforcement is interwoven by warp and weft yarns, which are spun by short fibers. The multi-scale composite structure made tensile properties challenging to predict. To provide the prediction of woven fabric reinforced composites, the macro and micro ramie fiber reinforced composites fabricated by multi-layer ramie plain woven fabrics, single-layer fabric, and detached yarn were analyzed. Results demonstrated that tensile properties of composites in the warp direction are lower than that in the weft direction due to yarn crimp and weaving damage. The linear fracture behavior of various composites confirms the hierarchical relationship between internal structure and tensile properties. The actual yarn volume fraction in fabrics or composites is calculated and introduced to the ROM model. The improved ROM model significantly enhances the prediction accuracy and efficiency of ramie plain woven fabric reinforced composites in five different areal densities and two interwoven directions.